2014
DOI: 10.1371/journal.pone.0096083
|View full text |Cite
|
Sign up to set email alerts
|

A MAP3k1 SNP Predicts Survival of Gastric Cancer in a Chinese Population

Abstract: ObjectivesGenome-wide association studies (GWAS) have demonstrated that the single nucleotide polymorphism (SNP) MAP3K1 rs889312 is a genetic susceptibility marker significantly associated with a risk of hormone-related tumors such as breast cancer. Considering steroid hormone-mediated signaling pathways have an important role in the progression of gastric cancer, we hypothesized that MAP3K1 rs889312 may be associated with survival outcomes in gastric cancer. The purpose of this study was to test this hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…MAP3K1 is a component of an evolutionarily conserved signal transduction cascade, which can activate mitogen-activated protein kinases (MAPKs) (39). It has been previously revealed that the single nucleotide polymorphism MAP3K1 rs889312 is closely associated with the risk of breast cancer and outcome among patients with diffuse-type gastric cancer (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAP3K1 is a component of an evolutionarily conserved signal transduction cascade, which can activate mitogen-activated protein kinases (MAPKs) (39). It has been previously revealed that the single nucleotide polymorphism MAP3K1 rs889312 is closely associated with the risk of breast cancer and outcome among patients with diffuse-type gastric cancer (40).…”
Section: Discussionmentioning
confidence: 99%
“…GAPDH was used as endogenous control to normalize the expression data. Reactions were incubated for 10 min at 95˚C, followed by 40 (19).…”
Section: Reverse Transcription Quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…Recently, MAP3K1 rs889312 has been identified as a low-penetrant risk factor for breast cancer, both for ER+ or ER− breast cancer [ 18 ]. It was also demonstrated to be an independent risk factor for poor survival in diffuse-type gastric cancer in an overdominant model [ 19 ]. However, two similar investigations failed to prove this variant was associated with BC clinical outcome [ 6 , 7 ], although neither of them carried out survival analysis on the basis of BC intrinsic subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Only the SNP rs4135385 AG/AA genotypes were significantly associated with a favorable GC survival compared with the GG genotype (adjusted hazard ratio = 0.80; 95% confidence interval = 0.66-0.97), and the association was more prominent among patients with non-cardia GC than those with cardia GC (log-rank p = 0.007 for non-cardia GC and 0.417 for cardia GC). Polymorphisms in genes such as SCRN1, MTHFR, MAP3K1, TLR-9 and pri-let-7a-2 also have been demonstrated to be useful prognostic biomarkers for GC patients [32,41,42,43,44,45,46]. …”
Section: Discussionmentioning
confidence: 99%